Covalent bond bonded stannous sulfide / indium zinc sulfide composite material as well as preparation method and application thereof
The covalently bonded stannous sulfide/indium zinc sulfide composite material forms a Sn–S covalently bonded heterogeneous interface, which solves the problem of low catalytic activity of the indium zinc sulfide photocatalyst caused by the rapid recombination of photogenerated carriers. , significantly improves the performance of photocatalytic water splitting to produce hydrogen, and has the potential for stable and industrial application.
Patent Information
- Application Number
- CN202411435912.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing indium zinc sulfide photocatalysts have low catalytic activity due to the rapid recombination of photogenerated electrons and holes during the process of water decomposition and hydrogen production, and the heterogeneous interface contact is loose, resulting in low efficiency.
Through covalently bonded stannous sulfide/indium zinc sulfide composite materials, two-dimensional indium zinc sulfide nanosheets are loaded on one-dimensional stannous sulfide nanoribbons, forming a Sn–S covalently bonded heterogeneous interface to promote Separation and transfer of photogenerated carriers.
The performance of photocatalytic water splitting to produce hydrogen is significantly improved, and the problem of loose interface contact is overcome. The material has strong response to visible light, stable performance, and is suitable for industrial applications.
Smart Images

Figure CN119318974A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of a stannous sulfide / indium zinc sulfide composite material, and in particular to a covalently bonded stannous sulfide / indium zinc sulfide composite material and a preparation method and application thereof. Background Art
[0002] Driven by sunlight, using semiconductor materials as catalysts to decompose water into hydrogen is a green and effective hydrogen production technology, and it is also one of the most promising ways to achieve the conversion of solar energy into chemical energy. Semiconductor metal sulfides are an important class of materials for photocatalytic water decomposition to produce hydrogen. Among them, indium zinc sulfide, as a photocatalyst with a two-dimensional layered structure, has attracted widespread attention due to its simple preparation method, good visible light absorption ability and suitable band structure. However, the activity of pure indium zinc sulfide in photocatalytic hydrogen production is still severely limited by the rapid recombination of its own photogenerated electrons and holes. Stannous sulfide has excellent optoelectronic properties, such as a wide light absorption range from visible light to near-infrared light and a high electron migration rate. How to compound stannous sulfide and indium zinc sulfide to form an effective heterojunction is an important issue to improve its catalytic performance. Summary of the invention
[0003] In view of the defects of the above-mentioned prior art, the present invention provides a covalently bonded stannous sulfide / indium zinc sulfide composite material, which overcomes the problems of rapid recombination of photogenerated carriers, loose heterogeneous interface formation and low catalytic efficiency in existing catalytic materials. The present invention also provides a preparation method of the covalently bonded stannous sulfide / indium zinc sulfide composite material and its application.
[0004] The technical solution of the present invention is as follows: a covalently bonded stannous sulfide / indium zinc sulfide composite material, comprising a two-dimensional indium zinc sulfide nanosheet and a one-dimensional stannous sulfide nanobelt, wherein the two-dimensional indium zinc sulfide nanosheet is loaded on the one-dimensional stannous sulfide nanobelt, and the tin atoms in the stannous sulfide nanobelt are bonded to the sulfur atoms in the indium zinc sulfide nanosheet through covalent bonds.
[0005] Another technical solution of the present invention is: a method for preparing a covalently bonded stannous sulfide / indium zinc sulfide composite material, comprising the steps of:
[0006] (1) using a water-soluble tin source and a sulfur source as raw materials, performing a hydrothermal reaction in an alkaline aqueous solution, and after the reaction is completed, washing and vacuum drying to prepare a one-dimensional tin sulfide nanobelt;
[0007] (2) adding the one-dimensional tin sulfide nanobelt obtained in step (1) to the precursor solution of indium zinc sulfide, heating and stirring to react, and after the reaction is completed, washing and vacuum drying to prepare a covalently bonded tin sulfide / indium zinc sulfide composite material.
[0008] Furthermore, the tin source is selected from one of stannous chloride, stannous sulfate and stannous acetate; the sulfur source is selected from one of thioacetamide, thiourea, sodium thiosulfate and ammonium sulfide; and the alkaline aqueous solution is selected from one of urea aqueous solution, sodium hydroxide aqueous solution and sodium carbonate aqueous solution.
[0009] Furthermore, in the step (1), the molar ratio of the tin source to the sulfur source is 1:(10-30); and the molar concentration of the alkaline aqueous solution is 0.2-0.5 mol / L.
[0010] Furthermore, the temperature of the hydrothermal reaction in step (1) is 150-200° C., and the reaction time is 12-20 hours.
[0011] Furthermore, the precursor solution of indium zinc sulfide is obtained by dissolving zinc chloride, indium chloride tetrahydrate and thioacetamide in a mixed solvent of glycerol and water, the molar ratio of zinc chloride, indium chloride tetrahydrate and thioacetamide is 1:(2-5):(3-8), the pH value of the precursor solution of indium zinc sulfide is adjusted to 1-4 by dilute hydrochloric acid, and the volume ratio of glycerol to water is 1:(3-10).
[0012] Furthermore, the one-dimensional tin sulfide nanobelt is added to the indium zinc sulfide precursor solution at a mass ratio of 5% to 20% of the one-dimensional tin sulfide nanobelt in the covalently bonded tin sulfide / indium zinc sulfide composite material, preferably 10% to 15%.
[0013] Furthermore, the temperature of the heating and stirring reaction is 50-80° C., and the reaction time is 1-5 hours.
[0014] Furthermore, in the steps (1) and (2), the product is washed 3 to 6 times with water and ethanol respectively, and vacuum drying is performed at 50 to 80° C. for 10 to 20 hours.
[0015] Another technical solution of the present invention is the application of a covalently bonded tin sulfide / indium zinc sulfide composite material as a photocatalyst in photocatalytic water decomposition to produce hydrogen.
[0016] The advantages of the present invention compared with the prior art are:
[0017] (1) The covalently bonded tin sulfide / indium zinc sulfide composite material of the present invention is a covalent heterogeneous interface formed by two-dimensional indium zinc sulfide nanosheets supported on one-dimensional tin sulfide nanobelts by an in-situ growth method, which overcomes the problem of loose interface contact in heterojunction catalytic materials. The built-in electric field at the interface promotes the effective separation and rapid transfer of photogenerated electrons and holes through the formed Sn-S covalent bonds, significantly improving the performance of photocatalytic water decomposition to produce hydrogen.
[0018] (2) The morphology of the covalently bonded tin sulfide / indium zinc sulfide composite material of the present invention is a one-dimensional / two-dimensional structure. The advantages of this structure are: on the one hand, the fast and long-distance charge transport characteristics of the one-dimensional structure material can be used to further improve the separation efficiency of photogenerated carriers; on the other hand, the introduction of the one-dimensional tin sulfide nanobelts inhibits the aggregation of the two-dimensional indium zinc sulfide nanosheets themselves, which helps to expose abundant reactive active sites.
[0019] (3) The covalently bonded tin sulfide / indium zinc sulfide composite material of the present invention is a catalytic material with strong visible light response ability, high photocatalytic water decomposition hydrogen production effect, stable performance, and can be reused multiple times, and has good application prospects in the field of new energy.
[0020] (4) The preparation method of the covalently bonded tin sulfide / indium zinc sulfide composite material of the present invention is simple, the required raw materials are easily available, and the operation is simple and convenient, and it is suitable for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope (SEM) image of the tin sulfide nanobelt obtained in Example 1.
[0022] Figure 2 This is a transmission electron microscope (TEM) image of the tin sulfide nanobelt obtained in Example 1.
[0023] Figure 3 This is a SEM image of the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 1.
[0024] Figure 4 This is a TEM image of the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 1.
[0025] Figure 5 This is a high-resolution X-ray photoelectron spectroscopy (XPS) spectrum of the tin element in the tin sulfide nanobelts and the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 1.
[0026] Figure 6 This is the SEM image of the tin sulfide nanobelt obtained in Example 2.
[0027] Figure 7 This is a SEM image of the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 2.
[0028] Figure 8 This is the XPS spectrum of the tin element in the covalently bonded stannous sulfide / indium zinc sulfide composite material obtained in Example 2.
[0029] Fig. 9This is the SEM image of the tin sulfide nanobelt obtained in Example 3.
[0030] Fig.10 This is a SEM image of the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 3.
[0031] Fig.11 This is the XPS spectrum of the tin element in the covalently bonded stannous sulfide / indium zinc sulfide composite material obtained in Example 3.
[0032] Fig.12 This is the SEM image of the flower-shaped indium zinc sulfide obtained in the comparative example.
[0033] Fig.13 This is the TEM image of the flower-shaped indium zinc sulfide obtained in the comparative example.
[0034] Fig.14 The effect diagram of photocatalytic water decomposition to produce hydrogen is shown in Example 1 and covalently bonded tin sulfide / indium zinc sulfide composite materials of different mass ratios and the material prepared in Comparative Example 1.
[0035] Fig.15 The effect diagram of photocatalytic water decomposition to produce hydrogen by the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 1 and the tin sulfide nanobelt and flower-shaped indium zinc sulfide physical mixture obtained in Comparative Example 2.
[0036] Fig.16 This is a cycle effect diagram of the photocatalytic decomposition of water to produce hydrogen by the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 1. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the embodiments, but are not intended to limit the present invention.
[0038] Example 1
[0039] The preparation of one-dimensional tin sulfide nanobelts is carried out in the following specific steps:
[0040] First, 10 mmol of thioacetamide was added to 40 mL of urea aqueous solution (0.35 mol / L) and stirred until completely dissolved to obtain a uniform solution. Then, 0.6 mmol of stannous chloride dihydrate was added to the above solution and stirred for 30 min. Finally, the obtained mixed solution was transferred to a 50 mL high-pressure reactor, and the reactor was placed in a 170 ° C forced air drying oven for 16 h. After the reaction was completed and naturally cooled to room temperature, the product was washed with water and ethanol three times, and finally dried in a vacuum drying oven at 60 ° C for 12 h to obtain a one-dimensional structure of tin sulfide nanobelts.
[0041] Attached Figure 1 and Figure 2 They are SEM and TEM images of the tin sulfide nanobelts prepared in Example 1. It can be seen from the images that the prepared tin sulfide nanobelts present a one-dimensional ribbon structure with a smooth surface.
[0042] The preparation of the covalently bonded tin sulfide / indium zinc sulfide composite material is carried out in the following specific steps:
[0043] First, 32 mL of water (adjusted to pH 2.5 with 0.5 mol / L dilute hydrochloric acid) and 8 mL of glycerol were added to a 150 mL round-bottom flask, and a uniform solution was obtained by ultrasonication for 5 min. Then, 1 mmol of zinc chloride, 2 mmol of indium chloride tetrahydrate and 4 mmol of thioacetamide were added to the above solution in sequence and stirred for 15 min. Next, 14.1 mg of tin sulfide nanobelts were added to the above indium zinc sulfide precursor solution, ultrasonically dispersed for 15 min to obtain a uniform suspension, and then placed in an oil bath at 80 ° C for 2 h. After the reaction was completed and naturally cooled to room temperature, the product was washed with water and ethanol 3 times, and finally dried in a vacuum drying oven at 60 ° C for 12 h to obtain a series of tin sulfide / indium zinc sulfide composite materials, wherein the mass ratio of the one-dimensional tin sulfide nanobelt in the tin sulfide / indium zinc sulfide composite material was 15%.
[0044] Attached Figure 3 and Figure 4 They are SEM and TEM images of the covalently bonded tin sulfide / indium zinc sulfide composite material prepared in Example 1. From the images, it can be seen that the two-dimensional indium zinc sulfide nanosheets are evenly and tightly loaded on the surface of the one-dimensional tin sulfide nanobelts, showing a one-dimensional / two-dimensional structural feature.
[0045] Attached Figure 5 This is a high-resolution XPS spectrum of the tin element in the tin sulfide nanobelt and the covalently bonded tin sulfide / indium zinc sulfide composite material prepared in Example 1. It can be seen from the figure that compared with the tin sulfide nanobelt, the tin sulfide / indium zinc sulfide composite material has an obvious characteristic peak at a binding energy of 497.72 eV, corresponding to the mutual bonding of the tin atoms in tin sulfide and the sulfur atoms in indium zinc sulfide to form an interfacial Sn-S covalent bond.
[0046] Example 2
[0047] The preparation of one-dimensional tin sulfide nanobelts is carried out in the following specific steps:
[0048] First, 10 mmol of thioacetamide was added to 40 mL of urea aqueous solution (0.25 mol / L) and stirred until completely dissolved to obtain a uniform solution. Then, 1.0 mmol of stannous chloride dihydrate was added to the above solution and stirred for 30 min. Finally, the obtained mixed solution was transferred to a 50 mL high-pressure reactor, and the reactor was placed in a 150 ° C forced air drying oven for 20 h. After the reaction was completed and naturally cooled to room temperature, the product was washed with water and ethanol three times, and finally dried in a vacuum drying oven at 60 ° C for 12 h to obtain a one-dimensional tin sulfide nanobelt.
[0049] Attached Figure 6 This is a SEM image of the tin sulfide nanobelt prepared in Example 2. It can be seen from the image that the prepared tin sulfide nanobelt presents a one-dimensional ribbon structure with a smooth surface.
[0050] The preparation of the covalently bonded tin sulfide / indium zinc sulfide composite material is carried out in the following specific steps:
[0051] First, 35 mL of water (adjust the pH value to 1.5 with 0.5 mol / L dilute hydrochloric acid) and 5 mL of glycerol were added to a 150 mL round-bottom flask, and a uniform solution was obtained by ultrasonication for 5 min. Then, 1 mmol of zinc chloride, 3 mmol of indium chloride tetrahydrate and 6 mmol of thioacetamide were added to the above solution in sequence and stirred for 15 min. Next, 14.1 mg of tin sulfide nanobelts were added to the above indium zinc sulfide precursor solution, ultrasonically dispersed for 15 min to obtain a uniform suspension, and then placed in an oil bath at 60 ° C for 5 h. After the reaction was completed and naturally cooled to room temperature, the product was washed with water and ethanol 3 times, respectively, and finally dried in a vacuum drying oven at 70 ° C for 16 h to obtain a tin sulfide / indium zinc sulfide composite material.
[0052] Attached Figure 7 This is a SEM image of the covalently bonded tin sulfide / indium zinc sulfide composite material prepared in Example 2. From the image, it can be seen that the two-dimensional indium zinc sulfide nanosheets are evenly and tightly loaded on the surface of the one-dimensional tin sulfide nanobelts, showing a one-dimensional / two-dimensional structural feature.
[0053] Attached Figure 8 This is a high-resolution XPS spectrum of the tin element in the tin sulfide nanobelt and the covalently bonded tin sulfide / indium zinc sulfide composite material prepared in Example 2. As can be seen from the figure, the tin sulfide / indium zinc sulfide composite material has an obvious characteristic peak at a binding energy of 497.71 eV, which corresponds to the mutual bonding of tin atoms in tin sulfide and sulfur atoms in indium zinc sulfide to form an interfacial Sn-S covalent bond.
[0054] Example 3
[0055] The preparation of one-dimensional tin sulfide nanobelts is carried out in the following specific steps:
[0056] First, 15 mmol of thioacetamide was added to 40 mL of urea aqueous solution (0.45 mol / L) and stirred until completely dissolved to obtain a uniform solution. Then, 0.5 mmol of stannous chloride dihydrate was added to the above solution and stirred for 30 min. Finally, the obtained mixed solution was transferred to a 50 mL high-pressure reactor, and the reactor was placed in a 200 ° C forced air drying oven for 12 h. After the reaction was completed and naturally cooled to room temperature, the product was washed with water and ethanol three times, and finally dried in a vacuum drying oven at 60 ° C for 12 h to obtain a one-dimensional tin sulfide nanobelt.
[0057] Attached Fig. 9 This is a SEM image of the tin sulfide nanobelt prepared in Example 3. It can be seen from the image that the prepared tin sulfide nanobelt presents a one-dimensional ribbon structure with a smooth surface.
[0058] The preparation of the covalently bonded tin sulfide / indium zinc sulfide composite material is carried out in the following specific steps:
[0059] First, 30 mL of water (adjust the pH value to 3.5 with 0.5 mol / L dilute hydrochloric acid) and 3 mL of glycerol were added to a 150 mL round-bottom flask, and a uniform solution was obtained by ultrasonication for 5 min. Then, 1 mmol of zinc chloride, 5 mmol of indium chloride tetrahydrate and 8 mmol of thioacetamide were added to the above solution in sequence and stirred for 15 min. Next, 14.1 mg of tin sulfide nanobelts were added to the above indium zinc sulfide precursor solution, ultrasonically dispersed for 15 min to obtain a uniform suspension, and then placed in an oil bath at 70 ° C for reaction for 3 h. After the reaction was completed and naturally cooled to room temperature, the product was washed with water and ethanol 3 times, respectively, and finally dried in a vacuum drying oven at 80 ° C for 20 h to obtain a tin sulfide / indium zinc sulfide composite material.
[0060] Attached Fig.10 This is a SEM image of the covalently bonded tin sulfide / indium zinc sulfide composite material prepared in Example 3. From the image, it can be seen that the two-dimensional indium zinc sulfide nanosheets are evenly and tightly loaded on the surface of the one-dimensional tin sulfide nanobelts, showing a one-dimensional / two-dimensional structural feature.
[0061] Attached Fig.11 This is a high-resolution XPS spectrum of the tin element in the tin sulfide nanobelt and the covalently bonded tin sulfide / indium zinc sulfide composite material prepared in Example 3. As can be seen from the figure, the tin sulfide / indium zinc sulfide composite material has an obvious characteristic peak at a binding energy of 497.70 eV, which corresponds to the mutual bonding of tin atoms in tin sulfide and sulfur atoms in indium zinc sulfide to form an interfacial Sn-S covalent bond.
[0062] Comparative Example 1
[0063] The preparation of flower-shaped indium zinc sulfide, the specific steps are as follows:
[0064] First, 32 mL of water (adjusted to pH 2.5 with 0.5 mol / L dilute hydrochloric acid) and 8 mL of glycerol were added to a 150 mL round-bottom flask, and ultrasonicated for 5 min to obtain a uniform solution. Then, 1 mmol of zinc chloride, 2 mmol of indium chloride tetrahydrate, and 4 mmol of thioacetamide were added to the above solution in sequence, stirred for 15 min, and placed in an oil bath at 80 ° C for 2 h. After the reaction was completed and naturally cooled to room temperature, the product was washed with water and ethanol three times, respectively, and finally dried in a vacuum drying oven at 60 ° C for 12 h to obtain flower-shaped indium zinc sulfide.
[0065] Attached Fig.12 and Fig.13 These are the SEM and TEM images of the flower-ball-shaped indium zinc sulfide. From the pictures, it can be seen that the prepared indium zinc sulfide is assembled into a flower-ball-shaped structure by stacking a large number of two-dimensional nanosheets.
[0066] Comparative Example 2
[0067] The preparation of the physical mixture of tin sulfide nanobelts and flower-shaped indium zinc sulfide is carried out in the following specific steps:
[0068] 14.1 mg of the tin sulfide nanobelts obtained in Example 1 and 80 mg of the flower-shaped indium zinc sulfide obtained in Comparative Example 1 were placed in a mortar and ground for 30 minutes without any other treatment to obtain a physical mixture of the tin sulfide nanobelts and the flower-shaped indium zinc sulfide.
[0069] Performance comparison experiment
[0070] Photocatalytic decomposition of water to produce hydrogen, the specific steps are as follows:
[0071] Based on the preparation steps of Example 1, 4.2 mg, 8.9 mg and 20 mg of tin sulfide nanobelts were added to the precursor solution of indium zinc sulfide, and then ultrasonically dispersed for 15 minutes to obtain a uniform suspension, which was placed in an oil bath at 80°C for reaction for 2 hours. After the reaction was completed and naturally cooled to room temperature, the product was washed with water and ethanol three times, and finally dried in a vacuum drying oven at 60°C for 12 hours to obtain a tin sulfide / indium zinc sulfide composite material, wherein the mass proportions of the one-dimensional tin sulfide nanobelts in the tin sulfide / indium zinc sulfide composite material were 5%, 10% and 20%, respectively.
[0072] 10 mg of the one-dimensional tin sulfide nanobelt obtained in Example 1, the covalently bonded tin sulfide / indium zinc sulfide composite material of 5%, 10%, 15%, and 20% by mass ratio based on Example 1, the flower-shaped indium zinc sulfide obtained in Comparative Example 1, and the catalyst composed of the physical mixture of tin sulfide nanobelt and flower-shaped indium zinc sulfide obtained in Comparative Example 2 were dispersed in 100 mL of a mixed aqueous solution of sodium sulfite (0.35 mol / L) and sodium sulfide (0.25 mol / L) by ultrasonic dispersion, and then stirred for 30 minutes to obtain a uniform suspension. Then, the above suspension was evacuated for 30 minutes to exclude all air, and the temperature of the photocatalytic reaction system was maintained at 10°C using a condensation circulation system. Finally, a 300W xenon lamp was used as a light source, and the photocatalytic water decomposition reaction was continued for 5 hours under stirring conditions, and samples were collected once every 1 hour, and the amount of hydrogen produced under light was quantitatively detected by a gas chromatograph equipped with a thermal conductivity detector.
[0073] Attached Fig.14 The effect diagram of photocatalytic water decomposition and hydrogen production of prepared tin sulfide nanobelts, flower-shaped indium zinc sulfide, and covalently bonded tin sulfide / indium zinc sulfide composite materials with different mass ratios. It can be seen from the figure that the photocatalytic hydrogen production efficiency of the covalently bonded tin sulfide / indium zinc sulfide composite material is significantly higher than that of the single tin sulfide material and indium zinc sulfide material.
[0074] Attached Fig.15 The effect diagram of photocatalytic water decomposition and hydrogen production of the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 1 and the tin sulfide nanobelt and flower-shaped indium zinc sulfide physical mixture obtained in Comparative Example 2. As can be seen from the figure, the photocatalytic hydrogen production efficiency of the tin sulfide nanobelt and flower-shaped indium zinc sulfide physical mixture is significantly lower than that of the covalently bonded tin sulfide / indium zinc sulfide composite material, indicating that the heterogeneous interface formed by the Sn-S covalent bond can effectively improve the performance of photocatalytic water decomposition and hydrogen production.
[0075] Attached Fig.16 This is a cycle effect diagram of the covalently bonded tin sulfide / indium zinc sulfide composite material obtained in Example 1 for photocatalytic water decomposition to produce hydrogen. As can be seen from the figure, the material still shows a high hydrogen production after being used for 4 times, indicating that it has good cycle stability and potential application value.
Claims
1. A covalently bonded tin sulfide / indium zinc sulfide composite material, characterized in that: The invention comprises a two-dimensional indium zinc sulfide nanosheet and a one-dimensional tin sulfide nanobelt, wherein the two-dimensional indium zinc sulfide nanosheet is loaded on the one-dimensional tin sulfide nanobelt, and the tin atoms in the tin sulfide nanobelt are bonded to the sulfur atoms in the indium zinc sulfide nanosheet through covalent bonds.
2. A method for preparing the covalently bonded tin sulfide / indium zinc sulfide composite material according to claim 1, characterized in that: Includes steps: (1) using a water-soluble tin source and a sulfur source as raw materials, performing a hydrothermal reaction in an alkaline aqueous solution, and after the reaction is completed, washing and vacuum drying to prepare a one-dimensional tin sulfide nanobelt; (2) adding the one-dimensional tin sulfide nanobelt obtained in step (1) to the precursor solution of indium zinc sulfide, heating and stirring to react, and after the reaction is completed, washing and vacuum drying to prepare a covalently bonded tin sulfide / indium zinc sulfide composite material.
3. The method for preparing the covalently bonded tin sulfide / indium zinc sulfide composite material according to claim 2, characterized in that: The tin source is selected from one of stannous chloride, stannous sulfate and stannous acetate; the sulfur source is selected from one of thioacetamide, thiourea, sodium thiosulfate and ammonium sulfide; and the alkaline aqueous solution is selected from one of urea aqueous solution, sodium hydroxide aqueous solution and sodium carbonate aqueous solution.
4. The method for preparing the covalently bonded tin sulfide / indium zinc sulfide composite material according to claim 2, characterized in that: In the step (1), the molar ratio of the tin source to the sulfur source is 1:(10-30); and the molar concentration of the alkaline aqueous solution is 0.2-0.5 mol / L.
5. The method for preparing the covalently bonded tin sulfide / indium zinc sulfide composite material according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step (1) is 150-200° C., and the reaction time is 12-20 hours.
6. The method for preparing the covalently bonded tin sulfide / indium zinc sulfide composite material according to claim 2, characterized in that: The precursor solution of indium zinc sulfide is obtained by dissolving zinc chloride, indium chloride tetrahydrate and thioacetamide in a mixed solvent of glycerol and water, wherein the molar ratio of zinc chloride, indium chloride tetrahydrate and thioacetamide is 1:(2-5):(3-8), the pH value of the precursor solution of indium zinc sulfide is adjusted to 1-4 by dilute hydrochloric acid, and the volume ratio of glycerol to water is 1:(3-10).
7. The method for preparing the covalently bonded tin sulfide / indium zinc sulfide composite material according to claim 2, characterized in that: The one-dimensional tin sulfide nanobelt is added to the precursor solution of indium zinc sulfide in a mass ratio of 5% to 20% of the one-dimensional tin sulfide nanobelt in the covalently bonded tin sulfide / indium zinc sulfide composite material.
8. The method for preparing the covalently bonded tin sulfide / indium zinc sulfide composite material according to claim 2, characterized in that: The temperature of the heating and stirring reaction is 50-80° C., and the reaction time is 1-5 hours.
9. The method for preparing the covalently bonded tin sulfide / indium zinc sulfide composite material according to claim 2, characterized in that: In the steps (1) and (2), the product is washed 3 to 6 times with water and ethanol respectively, and vacuum dried at 50 to 80° C. for 10 to 20 hours.
10. An application of a covalently bonded tin sulfide / indium zinc sulfide composite material, characterized in that: The covalently bonded tin(II) sulfide / indium zinc sulfide composite material according to claim 1 is used as a photocatalyst for photocatalytic water decomposition to produce hydrogen.
Citation Information
Patent Citations
Cadmium sulfide-sulfur indium zinc heterojunction nanorod array composite material and preparation method thereof
CN114016077A
P-n type stannous sulfide-zinc stannate semiconductor material and preparation method and application thereof
CN114653382A
Efficient ZnIn2S4 / SnSe2 / In2Se3 photocatalytic water splitting hydrogen production catalyst
CN114797905A
Composite heterojunction photoelectrode and preparation method thereof
CN114855183A
The outer-race electric cart in which the balance auxiliary device is included
KR1020220029028A